2018
DOI: 10.1007/s00253-018-8904-x
|View full text |Cite
|
Sign up to set email alerts
|

The features that distinguish lichenases from other polysaccharide-hydrolyzing enzymes and the relevance of lichenases for biotechnological applications

Abstract: The main specific features of β-1,3-1,4-glucanases (or lichenases, EC 3.2.1.73), the enzymes that in a strictly specific manner hydrolyze β-glucans of many cereal species and lichens containing β-1,3 and β-1,4 bonds, are reviewed as well as the current strategies used for their protein design, which have been successfully applied to make lichenases more attractive and promising for biocatalytic conversion of biomass, in particular, in the areas of their biotechnological application, such as brewing industry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Thus, our data demonstrate a higher sensitivity of the fluorometric assay for lichenase quantification (15 ng in the preparation over 180-min incubation of lichenase with the substrate) as compared with the Somogyi-Nelson assay (to 2 µg in the preparation). As has been earlier demonstrated, thermostable lichenase is rather resistant to various chemical reagents, retaining a high level of enzyme activity in the presence of EDTA, SDS, Triton X-100, and several others [9]. In addition, we compared the effects of several components contained in the buffers for extraction of soluble plant proteins on the modulation of lichenase quantification in samples using fluorometric and Somogyi-Nelson assays, namely, EDTA (50-100 mM), NaCl (10-100 mM), and SDS (0.1-0.5%).…”
Section: Comparative Analysis Of Thermostable Lichenase Quantification With Somogyi-nelson and Fluorometric Assaysmentioning
confidence: 74%
See 2 more Smart Citations
“…Thus, our data demonstrate a higher sensitivity of the fluorometric assay for lichenase quantification (15 ng in the preparation over 180-min incubation of lichenase with the substrate) as compared with the Somogyi-Nelson assay (to 2 µg in the preparation). As has been earlier demonstrated, thermostable lichenase is rather resistant to various chemical reagents, retaining a high level of enzyme activity in the presence of EDTA, SDS, Triton X-100, and several others [9]. In addition, we compared the effects of several components contained in the buffers for extraction of soluble plant proteins on the modulation of lichenase quantification in samples using fluorometric and Somogyi-Nelson assays, namely, EDTA (50-100 mM), NaCl (10-100 mM), and SDS (0.1-0.5%).…”
Section: Comparative Analysis Of Thermostable Lichenase Quantification With Somogyi-nelson and Fluorometric Assaysmentioning
confidence: 74%
“…The ability to refold in vitro after heat treatment at 70 • Cor ethanol denaturation can be used for rapid and cost-efficient purification of plant protein lysates, in particular, when utilizing lichenase in plant biotechnology. For example, it has been shown that the heat treatment at 70 • Cremoves up to 50% of contaminating plant proteins, while lichenase and the proteins fused to lichenase remain intact [9,28]. The C. thermocellum thermostable lichenase is active in a wide range of temperatures and pH [29], while the thermostable lichenase preparations isolated from biological samples, in particular, from plants, retain their high specific activity during a long-term storage in a container of a closed system under changing temperature or during a thawing-freezing procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of this gene, Cel12A, belongs to the glycosyl hydrolase family 12 (GH12) and was found to be a lichenase-like or non-typical cellulase showing low activity on cellulose but high activity on lichenan (β-1,3-1,4-glucan) and barley mixed glucans ((1 → 3, 1 → 4)-β-D-glucans). These properties show the potential application of Cel12A in the brewing and wine industries to facilitate filtration processes; in animal foodstuffs to improve β-glucans digestibility and nutritive quality; to produce valuable oligosaccharides; and in the processing of agricultural and industrial wastes for producing bioethanol and biodiesel (Thomas 1956;Goldenkova-Pavlova et al 2018;Chaari and Ellouz Chaabouni 2019). The aim of the present work was to study (real-time RT-qPCR) the effect of different carbon sources and initial pH values on the expression of cel12A.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes act synergistically: endo-acting enzymes generate new reducing and non-reducing chain ends for the exo-acting enzymes, which release cellobiose that is further converted to glucose by β-glucosidases [ 15 ]. The above-mentioned enzymes involved in cellulose hydrolysis are also active on mixed-linked β-glucans along with lichenases (β-1,3−1,4-glucanase, EC 3.2.1.73), which specifically cleave β-1,4 glycoside bonds in 3-O substituted glucosyl residues, and β-1,3(4)-glucanases (EC 3.2.1.6), which act on β-1,3 or β-1,4 linkages when the glucose residues are substituted at C3 [ 16 ]. The enzymes that break down carbohydrates are grouped, based on their structural similarity, into several glycoside hydrolase (GH) families in the CAZy database [ 17 ].…”
Section: Introductionmentioning
confidence: 99%